(untitled) (Raparin Journal of Humanities (RJH), 2022)
The echo of the grammatical melody continued in the recitation of the Almighty’s saying: “God is innocent of the polytheists and His Messenger” [al-Tawbah: 3] They restricted grammar to knowledge of the movement of the end of words, and the care of movements remained their preoccupation and the focus of their attention until they determined the function of a word in the text and its significance with the type of movement that appears at the end of that word, and this is the correctness in most of the structures of Arabic speech, But this interest turned away from its goal, and became a sign of the grammarians’ ingenuity in presenting interpretations and narrating opinions in the explanation and explaining the reason for the movement of some of the structures mentioned in the speech of the Arabs, but it was sometimes tainted by the distance from the spirit of language and strangeness in mentioning interpretations and arbitrariness in reasoning, as the Arabic language whale A group of words that diminished the role of the movement in approving its function due to the specificity of those words, and there is no doubt in that. On the contrary, as the opposite of logic is that defining the function is complicated by the type of movement; And how not? And functions more than the three inflectional movements. We have observed issues in Arabic grammar that occupied a wide area of ​​the attention of the early grammarians, so they made a great effort in extracting and interpreting them and showed proficiency and mastery in listing the permissible and potential faces for each issue. There is a star in it that urged us to reconsider many interpretations, interpretations and conclusions that we think are far from the spirit of the language and the purpose of the speaker. We also noted the shortcomings of the movement’s role in defining the function in most of the issues that witnessed a plurality of the movement and the same function. In the following pages, we will present some of them in three sections: the first: the variation in the action of letters and the compatibility of meaning, the second: the implementation and cancellation of letters and the meaning is one, and the third: the change of movement and the stability of meaning.